2002
DOI: 10.1093/hmg/11.11.1351
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial protein frataxin prevents nuclear damage

Abstract: The mitochondrial protein frataxin helps maintain appropriate iron levels in the mitochondria of yeast and humans. A deficiency of this protein in humans causes Friedreich's ataxia, while its complete absence in yeast (Dyfh1 mutant) results in loss of mitochondrial DNA, apparently due to radicals generated by excess iron. We found that the absence of frataxin in yeast also leads to nuclear damage, as evidenced by inducibility of a nuclear DNA damage reporter, increased chromosomal instability including recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 59 publications
(82 reference statements)
3
59
0
1
Order By: Relevance
“…Frataxin has been described to reduce accumulation of ROS when overexpressed in non-transformed fibroblasts (16), and its yeast homologue Yfh1 has been shown to prevent damage to nuclear as well as mitochondrial DNA in Saccharomyces cerevisiae (17,18). Furthermore, mice lacking frataxin in pancreatic ␤ cells (23) or hepatocytes 4 exhibit an increased expression of oxidative stress markers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frataxin has been described to reduce accumulation of ROS when overexpressed in non-transformed fibroblasts (16), and its yeast homologue Yfh1 has been shown to prevent damage to nuclear as well as mitochondrial DNA in Saccharomyces cerevisiae (17,18). Furthermore, mice lacking frataxin in pancreatic ␤ cells (23) or hepatocytes 4 exhibit an increased expression of oxidative stress markers.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have previously shown that frataxin may influence the formation and accumulation of ROS in yeast, cultured mammalian cells, rodents, and finally humans (13)(14)(15)(16)(17)(18)23). Nevertheless, recent findings question the primary relevance of ROS formation in frataxin deficiency (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Moreover, it is found that DNA damage-inducible nuclear genes were highly expressed in cells lacking frataxin, suggesting that frataxin has a protective role in the nucleus and mitochondria to detoxify reactive oxygen species (Karthikeyan et al 2002).…”
Section: Functions and Regulation Of Iron Metabolism In Mitochondriamentioning
confidence: 99%
“…Frataxin was first identified as the protein deficient in Friedreich ataxia, a neuro-and cardiodegenerative disease (12). Studies in Saccharomyces cerevisiae have shown that defects in yeast or human frataxin are associated with the accumulation of iron in mitochondria and oxidative damage to both mitochondrial and nuclear DNA as well as to the iron-sulfur centers of mitochondrial aconitase and other respiratory enzymes (10,14,15,34). Similarly, mouse models in which the frataxin gene is selectively inactivated in neuronal or cardiac tissue present multiple respiratory enzyme deficits and accumulate iron in mitochondria in a time-dependent manner (16).…”
mentioning
confidence: 99%